Cytoskeleton disruption and plasma membrane damage determine methuosis of normal and malignant cells - Bin Dong; Jing Xiao; Junqi Wang; Xinhao Song; Hui Ji; Jiurong Peng; Xinru Weng; Dawei Guo; Shanxiang Jiang; Xiuge Gao (Cell & Bioscience)
Abstract Background Methuosis represents a novel cell death modality characterized by catastrophic cytoplasmic vacuolization in normal and malignant cells. However, the critical role and the underlying mechanism of cytoskeleton and plasma membrane damage in methuotic cells are largely unknown. Results We found that cytoskeleton protein F-actin, α-tubulin, β-tubulin and filamin A/B were disrupted in a reversible-dependent manner. In addition, RhoA-ROCK1 signaling pathway mediated cytoskeleton disruption in methuotic cells. Excessive cytoplasmic vacuolization triggered cellular plasma membrane damage and the release of damage associated molecular patterns (DAMPs), including lactate dehydrogenase (LDH), adenosine triphosphate (ATP) and calreticulin (CRT). Furthermore, at the end phase of methuotic cells, plasma membrane was damaged independent of pore-forming protein phosphorylation mixed lineage kinase domain-like (p-MLKL) and gasdermin D (GSDMD). Endosomal sorting complex required for transport (ESCRT)-III especially its subunit charged multivesicular body protein 3 (CHMP3) and charged multivesicular body protein 5 (CHMP5) negatively regulated excessive vacuolization-induced plasma membrane damage in cells undergoing methuosis. Conclusions The critical role and potential mechanism of cytoskeleton and plasma membrane damage in methuotic cells are known, which would facilitate the employment of methuosis in life science and pharmacology. Graphical Abstract